Production Inventory Model for Time Dependent Holding Cost, Selling Price Demand Rate, Controllable Deterioration Rate, and Multiple Market Demand with Shortages (Journal of Informatics and Mathematical Sciences, 2024)
For current competitive market conditions, the production system must produce the ideal product. A production system’s ability to produce a flawless final product depends critically on the quality of its raw materials. Using an excellent production-inventory model of a producer of a decaying item distributing goods to several markets with varying selling seasons, this article has investigated this issue. We have provided a solution approach to determine the best creation plan for finished goods and the best production plan for raw materials. For decaying items, a deterministic inventory model is created where shortages are permitted. In this model, the mandate rate is constant, and holding cost is a linear occupation of time. The purpose of this paper is to create a production-inventory model of instantaneous deteriorating items with multiple-market requests and controllable deterioration rates. Highlights of the model are to lower the overall cost of an inventory; this article has taken an analytical method. Lastly, a sensitivity analysis was conducted to investigate how various model parameters would affect the best course of action. Furthermore, we have elucidated mathematical models and assessed affectability to validate the identified models. Based on the model analysis, business enterprises can optimize the entire inventory price of deteriorating items inventory with a controllable deterioration rate. The model’s solution is shown to be fairly stable. to determine the best time to restock raw supplies and the best way to produce finished goods.